Tidal variation modulates the dissolved silicate behavior and exchange flux across the semi-enclosed bay‐coastal water continuum, China - Zhang, Peng; Xie, Jiale; Zhang, Jibiao; Fu, Miaojian; Luo, Weisheng; Cheng, Mingyue (Frontiers in Marine Science, 2023)
Coastal water is the key transition zone for the circulation and transport of nutrients. Their role in transporting nutrients is important to understanding global dissolved silicate (DSi) cycles and sources of nutrients supporting the biological pump and ocean carbon cycle. However, the understanding of controlling DSi exchange flux between the semi-enclosed bay and coastal water was still scarcely due to limitations in continuous observation. In this study, we conducted continuous investigations during spring tide (ST) and neap tide (NT) in 2021 in Shuidong Bay (SDB), China, to explore the impacts of different tidal cycles on DSi in SDB and the fluxes across SDB and South China Sea (SCS) coastal water. The findings demonstrated that there were significant differences in DSi concentrations and nutrients ratios between ST and NT in S1 station (P < 0.05). In addition, the DSi concentrations were 32.01 ± 27.21 μmol/L and 51.48 ± 48.44 μmol/L in ST and NT, respectively. Besides, the net export of DSi from SDB to SCS was 0.18 t throughout the entire early of autumn tidal cycle, suggesting SDB was the source of DSi, and its behavior across the semi-enclosed bay‐coastal water continuum was largely controlled by tidal characteristics (tidal height, flow velocity), water physicochemical parameters (salinity, pH), biological uptake and terrestrial sources input. SDB in ST has higher proportions of DSi: DIN (dissolved inorganic nitrogen) (1.49 ± 1.28) and DSi: DIP (dissolved inorganic phosphorus) (58.6 ± 43.73) compared with NT, DSi: DIN and DSi: DIP for the NT period were 1.45 ± 1.15 and 43.99 ± 28.59, indicating that phosphorus (P) is the limiting trophic factor for SDB. The tidal cycle in SDB would alter the DSi stoichiometry and mitigated the impact of eutrophication caused by terrestrial sources. This study provides new insights in the Si tidal cycling across the semi-enclosed bay‐coastal water continuum, which was implications for understanding DSi biogeochemical process and primary production dynamics in coastal water.